Belowground responses of woody plants to nitrogen addition in a phosphorus-rich region of northeast China - Guo, Jing; Gao, Yingzhi; Eissenstat, David M.; He, Chunguang; Sheng, Lianxi (Trees (Berlin, West), 2020)
Key Message Nitrogen addition leads to large increases in shoot growth but limited increases in root growth and reductions in mycorrhizal colonization of Sorbus pohuashanensis and Acanthopanax sessiliflorus. Soil in the cultivated fields of Changbai Mountain region of China is rich in phosphorus (P) and deficient in nitrogen (N) for most woody plants. However, currently N deposition is increasing and reducing its limitation on plant growth. How N addition shifts carbon investment among shoots, roots and arbuscular mycorrhizal (AM) fungi is not well understood, especially in woody plants growing in the field. We examine the responses of the growth, biomass partitioning and AM colonization of Sorbus pohuashanensis Hedl. and Acanthopanax sessiliflorus Seem. to low and high N fertilization in northeastern China on high-P soil over 3 years. With N addition, both plants increased shoot biomass by 20–45%, and N and P content by 13–30%, while root biomass increased only by 2.1–5.4%. The slower increase in root growth relative to shoot growth resulted in lower root mass fraction. After plant size (ontogeny) was accounted for, root mass fraction still decreased significantly with high N fertilization in both species. Mycorrhizal colonization intensity and AM-colonized root length decreased with an increase in N addition. In this P-rich site, the limited increase in root biomass and large decrease in AM colonization with N addition presumably promoted plant growth and nutrient uptake. Our results imply that the growth of these two species may be improved by increased carbon allocation to shoots, as N addition permitted sufficient nutrient uptake by roots and AM fungi to meet shoot nutrient demand without additional belowground carbon expenditure.